Tuning Cascade PID Controller for Valves Using optimization Methods - Gurel, Yusuf; Yildirim, Tulay (2020 Innovations in Intelligent Systems and Applications Conference (ASYU), 2020)
Precise control of proportional valves is an important subject for industry. In this work, we implemented and evaluated three different population-based heuristic optimization methods from literature and propose two different fitness functions to tune the closed-loop gains of a cascade PID flow and current control system for a directional proportional valve for operating hydraulic axes. Lastly we reached under 0.1% total steady state error at minimum.